Dose–Volume and Radiobiological Model-Based Comparative Evaluation of the Gastrointestinal Toxicity Risk of Photon and Proton Irradiation Plans in Localized Pancreatic Cancer Without Distant Metastasis - Raturi, Vijay P.; Tochinai, Taku; Hojo, Hidehiro; Rachi, Toshiya; Hotta, Kenji; Nakamura, Naoki; Zenda, Sadamoto; Motegi, Atsushi; Ariji, Takaki; Hirano, Yasuhiro; Baba, Hiromi; Ohyoshi, Hajime; et al. (Frontiers in Oncology, 2020)
Background: Radiobiological-model-based studies of photon-modulated radiotherapy for pancreatic cancer have reported reduced gastrointestinal (GI) toxicity, although the risk is still high. The purpose of this study was to investigate the potential of 3D-passive scattering proton beam therapy (3D-PSPBT) in limiting GI organs at risk (OARs) toxicity in localized pancreatic cancer based on dosimetric data and a normal tissue complication probability (NTCP) model. Methods: The data of 24 pancreatic cancer patients were retrospectively analyzed, and these patients were planned with intensity-modulated radiotherapy (IMRT), volume-modulated arc therapy (VMAT), and 3D-PSPBT. The tumor was targeted without elective nodal coverage. All generated plans consisted of a 50.4 GyE (Gray equivalent) dose in 28 fractions with equivalent OARs constraints, and they were normalized to cover 50% of the planning treatment volume (PTV) with 100% of the prescription dose. Physical dose distributions were evaluated. GI-OAR toxicity risk for different endpoints was estimated by using published NTCP Lyman Kutcher Burman (LKB) models. Analysis of variance (ANOVA) test was performed to compare the dosimetric data, and ∆NTCPIMRT-PSPBT and ∆NTCPVMAT-PSPBT were also computed. Results: Similar homogeneity and conformity for clinical target volume (CTV) and PTV were exhibited by all three planning techniques (P >0.05). 3D-PSPBT resulted in a significant dose reduction for GI-OARs in both the low-intermediate dose range (below 30 GyE), and the highest dose region (Dmax and V50GyE) in comparison with IMRT and VMAT (P <0.05). Based on the NTCP evaluation, the NTCP reduction for GI-OARs by 3D-PSPBT was minimal in comparison with IMRT and VMAT. Conclusion: 3D-PSPBT results in minimal NTCP reduction and has less potential to substantially reduce the toxicity risk of upper GI bleeding, ulceration, obstruction, and perforation endpoints, compared to IMRT and VMAT. 3D-PSPBT may have the potential to reduce acute dose-limiting toxicity in the form of nausea, vomiting, and diarrhea by reducing GI-OARs treated volume in the low to intermediate dose range. However, this result needs to be further evaluated in future clinical studies.